Illiquidity, duration and momentum profits: Evidence from the Korean stock market - Jaewan Bae; Changjun Lee (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2021)
This paper examines the role of illiquidity and duration factor in understanding the momentum profit in the Korean stock market. We find that the foreigner/institutional illiquidity factor explains the momentum effect. In addition, this paper finds that duration factor defined as the difference in returns of short-duration and longduration stocks captures well the momentum profits. That is, a two-factor model with the market and duration factor performs much better than competing asset pricing models in explaining the momentum effect. Finally, when controlling for the duration factor, the explanatory power of the foreign/institutional illiquidity factor on the momentum profits disappears. In sum, our empirical finding indicates that the duration factor is the most important ingredient in understanding the momentum effect in the Korean stock market.
Keywords: G11; G12; G14; 330; Duration; Market liquidity; Momentum effect; Duration factor; Illiquidity factor